2018
DOI: 10.1016/j.celrep.2018.06.067
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between PKCα and PI3K/AKT Signaling Is Tumor Suppressive in the Endometrium

Abstract: SUMMARY Protein kinase C (PKC) isozymes are commonly recognized as oncoproteins based on their activation by tumor-promoting phorbol esters. However, accumulating evidence indicates that PKCs can be inhibitory in some cancers, with recent findings propelling a shift in focus to understanding tumor suppressive functions of these enzymes. Here, we report that PKCα acts as a tumor suppressor in PI3K/AKT-driven endometrial cancer. Transcriptional suppression of PKCα is observed in human endometrial tumors in assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 50 publications
(77 reference statements)
8
40
0
Order By: Relevance
“…Cells were lysed in 50 mM Tris-HCl, pH 7.4, 100 mM NaCl, 1% Nonidet P-40, 2 mM EDTA, 0.1% SDS, 50 mM NaF, 10 mM Na3VO4, 1 mM phenylmethylsulfonyl fluoride, 25 μg/mL β-glycerophosphate, and one protease inhibitor mixture tablet from Roche, and extracts (30 μg protein) were analyzed by Western blotting as described [58]. Primary antibodies were from Cell Signaling [PARP: 95425; Caspase 7: 128275; GAPDH: 5174; HDAC1: 3565; HDAC2: 51135; HDAC3 39495; HDAC4: 7628; HDAC5: 204585; HDAC6: 76125; acetyl-α-tubulin (Lys40): 5335; acetyl-histone 3: 9649; cleaved caspase 3: 9664].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were lysed in 50 mM Tris-HCl, pH 7.4, 100 mM NaCl, 1% Nonidet P-40, 2 mM EDTA, 0.1% SDS, 50 mM NaF, 10 mM Na3VO4, 1 mM phenylmethylsulfonyl fluoride, 25 μg/mL β-glycerophosphate, and one protease inhibitor mixture tablet from Roche, and extracts (30 μg protein) were analyzed by Western blotting as described [58]. Primary antibodies were from Cell Signaling [PARP: 95425; Caspase 7: 128275; GAPDH: 5174; HDAC1: 3565; HDAC2: 51135; HDAC3 39495; HDAC4: 7628; HDAC5: 204585; HDAC6: 76125; acetyl-α-tubulin (Lys40): 5335; acetyl-histone 3: 9649; cleaved caspase 3: 9664].…”
Section: Methodsmentioning
confidence: 99%
“…Among down-regulated gene sets, we found genes associated with the tumor suppressors Atf2 , Pten , Pkca , P53 , and Rps14 , a negative regulator of c-Myc . Furthermore, genes associated with polycomb-repressive complex 1 (PRC1) were also down-regulated as well as mTORC1-regulated genes ( 39 , 40 , 41 , 42 , 43 , 44 ). Together, these data suggest that ALK-induced transformation and lymphomagenesis involves the induction of additional oncogenic pathways and the repression of tumor suppressive genes.…”
Section: Resultsmentioning
confidence: 99%
“…In USC, PIK3CA mutation occurs in about 30% of cases (11,(34)(35), which is consistent with the involvement of the PI3K-Akt signaling pathway seen from our analysis. Inhibition of PI3K/AKT/mTOR signaling strongly suppresses EEC progression (36)(37)(38) and clinical trials targeting PI3K/AKT/mTOR signaling in solid tumors have shown promise (39). However, the bene ts of this against in endometrial cancers is controversial due to the complexity of pharmacological action and toxicity (40).…”
Section: Discussionmentioning
confidence: 99%